Effects of Supervision on the Efficiencies of Banks in India in the Reform Period: A DEA Approach - Paul, Sheen (2005)
This study uncovers the performance of banks in India following liberalisation of the nation’s economy in 1991. Emphasis is placed on supervisory regulations and its consequent impact on bank efficiency. Elements of supervisory aspects relating to both the pre-liberalisation and post-liberalisation period were used to assess bank performance. The analytical technique used was ‘Data Envelopment Analysis’. It was observed from the analysis that foreign banks, amongst the other bank groups such as the state owned and private banks, were the most efficient, which was primarily a result of the policies that were enforced prior to liberalisation.